2011
DOI: 10.1097/phm.0b013e318214f699
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluations of Morphologic Changes of Gastrocnemius Muscle Fascicles and Achilles Tendon in Children with Cerebral Palsy

Abstract: The changes in Achilles tendon properties could be a result of adaptation to calf muscle fascicle shortening and stiffening, which may affect performance of the muscles. A better understanding of the interactions between calf muscle fascicles and Achilles tendon in children with CP may help treat the pathologic changes more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 21 publications
8
57
0
Order By: Relevance
“…Our results confirm those obtained in previous studies which report significantly shorter fascicle lengths in children with CP compared to controls (Gao et al, 2011;Mohagheghi et al, 2008). The shorter fascicles cannot be explained by shorter muscles in CP group children, since leg length and gastrocnemius muscle lengths were not different between the two groups of subjects.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results confirm those obtained in previous studies which report significantly shorter fascicle lengths in children with CP compared to controls (Gao et al, 2011;Mohagheghi et al, 2008). The shorter fascicles cannot be explained by shorter muscles in CP group children, since leg length and gastrocnemius muscle lengths were not different between the two groups of subjects.…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have focused on passive fascicle length measurements in spastic muscles of CP patients using ultrasound imaging, but the results have been inconsistent. Some studies reported significantly shorter fascicle lengths in spastic compared to control muscles (Gao et al, 2011;Mohagheghi et al, 2008), while others reported no differences between patients with CP and appropriate control group subjects (Malaiya et al, 2007;Shortland et al, 2002). Measurements of fascicle lengths in the triceps surae group have typically been made with the ankle joint in the resting (relaxed) position, where the muscle tension between agonists and antagonists is the same and likely close to zero.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This similar change was also demonstrated in the hemiplegic side of stroke patients 2 months after injection when the US examination was performed in the resting ankle position with knee extension 11. According to previous studies, the FL and FA of GCM changed systematically with knee and ankle position 26,28. However, the ankle and knee positions, along with the subject's position during the US imaging, were not the same across studies 11,12,14.…”
Section: Discussionsupporting
confidence: 75%
“…Some reports revealed no differences in FL between children with CP and typically-developing children and between paretic and non-paretic limbs,1,12,20,25,26 whereas others demonstrated a significant reduction in FL in spastic muscle 9,10. However, there are only a few reports about FL in children with CP.…”
Section: Discussionmentioning
confidence: 99%